Bank Stability and Its Determinants in The Nepalese Banking Industry - Singh, Nirmal (NRB Economic Review, 2021)
This paper investigates bank stability and its bank-specific, industry-specific, macroeconomic and institutional determinants for the Nepalese banking industry. The study employs the system GMM to a panel of bank-level data covering the period from 2004-2018. The results show that the stability of the Nepalese banking industry improved during the early years of the study period, i.e., 2004-2007; however, it exhibited a decaying trend for the rest of the study period. The analysis reveals that the major factors responsible for this deterioration are capital adequacy, asset quality, and earnings of the banks. Most of the dimensions have shown improvements during the initial years of the study period; however, this trend reversed post-2007.The study groups the banks into three categories: stable, moderately stable, and less stable banks as per their respective stability score. The estimation results indicate that a positive bank stability persistence exists in the Nepalese banking industry. Results suggest that credit growth has a negative impact on the stability of the banks. The results of the study support the concentration-stability hypothesis. Income diversification appears to have a positive impact on the stability of the banks. Findings disclose that inflation is playing a crucial role in impacting the stability of the banks. The study reveals that the GFC had no significant impact on the stability of the Nepalese banking industry.